(untitled) (International Journal of Engineering and Computer Science, 2014)
Human age, as an important personal trait, can be directly inferred by distinct patterns emerging from the facial appearance. Computer-based age synthesis and estimation via faces have become particularly prevalent topicsy because of their explosively emerging real-world applications, such as forensic art, electronic customer relationship management, security control and surveillance monitoring, biometrics, entertainment, and cosmetology. Age synthesis is defined to rerender a face image aesthetically with natural aging and rejuvenating effects on the individual face. Automatic age-progression is the process of modifying an image showing the face of a person in order to predict his/her future facial appearance.Age estimation is defined to label a face image automatically with the exact age (year) or the age group (year range) of the individual face. During growth, aging is affected in two main forms, one is the size and shape variation and the other is the textural variation. In this paper, we use the textural variation of the face during the growth, which appear more in the adulthood in theform of wrinkles.